Efektifitas Metode Story Telling Dalam Pemberian Pendidikan Kesehatan Cuci Tangan Yang Benar Terhadap Kemampuan Anak Usia Dini Pra Sekolah Diwilayah Kerja Pukesmas Jembatan Kecil - Susanti, Meri Epriana; Pebriani, Emi; Marlianto, Nuche (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
Background: Children aged 4 to 6 years. Called preschool children, at this time children have a great sense of curiosity, children are unique, like to imagine, and believe that they have power. At this stage, one of the characteristics of psychosocial development at this age is the expansion of the child's social environment, children begin to feel the need to have playmates, and have regular activities outside the home environment. With activities that often play outside the home, children are usually very susceptible to disease because children are lazy to wash their hands because washing hands for children is boring. Therefore, hand washing health education is needed with the Story Telling Method which can provide an understanding that washing hands is fun. Purpose: The purpose of this study was to identify the Effectiveness of the Story Telling Method in Providing Correct Hand Washing Health Education on the Abilities of Pre-School Early Childhood in the Jembatan Kecil Health Center Work Area Method: This study uses quantitative methodology using quasi-experimental techniques. A total of 32 preschool children aged 4 to 6 years in the work area of ​​the small bridge health center using a random sampling method. We used a univariate test, namely a paired t-test to assess the effect, and an independent t-test to assess the effectiveness of the Results: This study found that handwashing health education is effective with the Story Telling method in Preschool Early Childhood. 95% confidence interval. handwashing ability before being treated was 1.00 with SD = 0.000 and handwashing ability after being treated was 2.30 with SD = 0.520. The p-value = 0.000, it can be concluded that there is a difference between handwashing ability before and after being given health education with the story telling method. Conclusion: Handwashing health education with the Story Telling method can be used to change children's perceptions, allowing knowledge to be the basis for evaluating the actions taken.